2020
DOI: 10.4049/jimmunol.1900456
|View full text |Cite
|
Sign up to set email alerts
|

IL-7R–Dependent Phosphatidylinositol 3-Kinase Competes with the STAT5 Signal to Modulate T Cell Development and Homeostasis

Abstract: T cell development and homeostasis requires IL-7R α-chain (IL-7Rα) signaling. Tyrosine Y449 of the IL-7Rα is essential to activate STAT5 and PI3K, whereas PI3K recruitment requires IL-7Rα methionine M452. How IL-7Rα activates and regulates both signaling pathways differentially remains unclear. To characterize differential signaling, we established two lines of IL-7Rα mutant mice: IL-7R–Y449F mice and IL-7R–M452L mice. IL-7R–Y449F mice showed decreased PI3K and STAT5 signals, whereas IL-7R–M452L mice showed de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…Therefore, highlighting a key pathway in immune response that is epigenetically suppressed in ex vivo human GBM samples may serve more efficient development of biological therapies in the future. IL-7 has been identified as a key cytokine in the compensatory reaction to declining lymphocytes [ 28 , 29 ]. While exogenous administration of IL-7 could elevate the CD4+ and CD8+ T-cell counts, higher doses of this cytokine are associated with significant toxicity [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, highlighting a key pathway in immune response that is epigenetically suppressed in ex vivo human GBM samples may serve more efficient development of biological therapies in the future. IL-7 has been identified as a key cytokine in the compensatory reaction to declining lymphocytes [ 28 , 29 ]. While exogenous administration of IL-7 could elevate the CD4+ and CD8+ T-cell counts, higher doses of this cytokine are associated with significant toxicity [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…IL-7 receptor complex could activate PI3K/Akt/mTOR signaling pathway in lung cancer cell line and leukemia transformation cell line [ 34 , 35 ]. IL-7 receptor-dependent PI3K also competed with STAT5 signal to regulate T cell development and homeostasis in mice [ 36 ]. Taken together, IL-7 induced an increase in sCD27 mRNA variant in CD8 + T cells and release of sCD127 by CD8 + T cells probably through PI3K signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that the increased expression of LDHA in the most invasive subgroup of the hypoxia group activates the PI3K pathway, which promotes the invasion and metastasis of pancreatic cancer by regulating the differentiation, proliferation, metabolism, and stress of pancreatic cancer cells under hypoxic conditions (Supplementary Figure S7). PI3K inhibitors can inhibit the LDHA-induced activation of the PI3K signaling pathway 52,53 , which may become a new candidate drug for the treatment of pancreatic cancer. The efficacy of PI3K inhibitors in pancreatic cancer will be further verified in subsequent experiments.…”
Section: Discussionmentioning
confidence: 99%